Handgrip Strength Attenuates the Adverse Effects of Overweight on Cardiometabolic Risk Factors Among Collegiate Students but Not in Individuals with Higher Fat Levels - Garcia-Hermoso, A (Nature Publishing Group, 2019)
The aims of this study are to (i) examine a clustered metabolic syndrome composite score (MetScore) and fatness among college students across body mass index (BMI) categories, and (ii) determine whether fit individuals have lower MetScores, fewer individual metabolic syndrome components, and lower fatness than unfit individuals across BMI categories. A total of 1,795 participants aged >18 years who participated in The FUPRECOL Study were selected for the present analyses. Handgrip strength was tested by a grip dynamometer and used to classify adults as fit or unfit. Among all participants, MetScore, percentage of body fat, and visceral adiposity increased linearly across the BMI categories among college students (all P < 0.001). Individuals who were overweight and fit had a lower MetScore (−0.6 SD; P = 0.02), body fat percentage (−2.6%; P < 0.001) and visceral adiposity (−0.2; P = 0.01) than unfit peers. Moderately fit obese individuals had significantly lower visceral fat levels than unfit obese peers (−3.0; P = 0.03). These results suggest that having adequate handgrip strength-a proxy of overall strength capacity-may attenuate obesity-related cardiometabolic risk. Moreover, weight loss should be recommended to all individuals with obesity, even among those who are currently considered fit. © 2019, The Author(s).